KONFLIK PENGELOLAAN LAHAN PLASMA SAWIT DI KABUPATEN SERUYAN TAHUN 2008 - 2013 - Jenie Tri Andanni; Muhammad Adnan; Wiwik Widayati (Journal of Politic and Government Studies, 2015)
Seruyan Regency is the one of regencies with a number of Oil Palm Company. As a consequnce, the government through the minister of agriculture has oblige the company to provide plasma land for people around the plantation 20% in minimum from total plantation wide-scale. In the implementation, still hard  for  the company to actuate it due to  multiple interpretations on figuring out the minister of agriculture regulation. This study was aimed for knowing the caused factor why its so hard to the company to actuated the regulation, people perception on plasma land policy and also the action that government take to solved the conflict.            This study used a qualitative research method, with an interview and literature study to collect data. Source of data that used in this study are primary and secondary data were then examined and analyzed with descriptive approach.            The results of these studies include, still there the different perception between the company and people to decide  the land area that will be the plasma land, the company wanted the plasma land built up outside the company plantation area while people wanted in reverse. Moreover, the other cause that the company cant actuated the plasma land were caused by 3 factors, licensing, capital and land. To solved this conflict, the government has take some actions by forming a handling team, make an appeal letter to the company and also empowering people.            The province government should be more assertive to enforce and more proactive to sosalize the regulation to the company as well as the people, the company can commited to increasing public welfare to all people around plantaion area and  people can make common cause by the company and can be empowered. Because if every single stakeholder can be cooperate, then conflict can be more easy to solved. Keywords: Conflict, Plasma Land, Perception